2020
DOI: 10.7759/cureus.9590
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nocturnal Enuresis Among Children Dwelling in Rural Areas of Sindh

Abstract: Bilal et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…In many studies, it was reported that the perspective of this disease changed with the increase in the education level of parents and they applied to the hospital for treatment in the early period. 1,5,6 In our study, a statistically highly significant difference was found between the education level of the parents and the time of application of the children with EN. It was found that as the education level of the parents increased, the age of appli-Max: Maximum; Min: Minimum.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In many studies, it was reported that the perspective of this disease changed with the increase in the education level of parents and they applied to the hospital for treatment in the early period. 1,5,6 In our study, a statistically highly significant difference was found between the education level of the parents and the time of application of the children with EN. It was found that as the education level of the parents increased, the age of appli-Max: Maximum; Min: Minimum.…”
Section: Discussionmentioning
confidence: 48%
“…There are many studies in the literature that found that families with low income have more children with EN. 1,3,[5][6][7] In addition, whether the parent employment status contributes to the income level of the family; There have also been studies suggesting that this changes the socio-cultural lifestyle and thus affects the prevalence of EN. 1,7 Similar to these studies, in our study, it were revealed that families with high income levels were referred to the outpatient clinic earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dolgun et al [16] found that socioeconomic development did not affect the prevalence of enuresis. However, several studies mentioned that low socioeconomic status is a consistent risk factor for the incidence of wetting problems [3,5,17]. Although NE is a common childhood problem, the mechanism of this condition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Anne ve babanın eğitim seviyesi arttıkça noktürnal enürezisin azaldığı bilinmektedir [21][22][23]. Çalışmamızda çocuklarda gece altını ıslatma konusundaki bilgi ile eğitim durumu arasındaki ilişki incelenmiş ve istatistiksel olarak ileri derecede anlamlı bir farklılık bulunmuş, ailelerin eğitim düzeyi arttıkça enürezis konusundaki bilgi düzeylerinin de arttığı saptanmıştır.…”
Section: Demografikunclassified
“…Sosyoekonomik açıdan değerlendirildiğinde; aylık geliri 2500 TL ve üzerinde olanlar ve il merkezlerinde yaşayanların enürezis ile ilgili bilgi düzeylerinin kasaba ve köyde yaşayanlar ve aylık geliri 2500 TL den daha düşük olanlarla karşılaştırıldığında anlamlı olarak daha yüksek olduğu saptanmıştır (sırasıyla p=0,001; p=0,002). Literatürde de çalışmamıza benzer şekilde sosyoekonomik durum ile enürezis arasındaki ilişkiyi araştıran çalışmaların çoğunda düşük sosyoekonomik düzeye sahip ailelerin çocuklarında enürezis sıklığının arttığı bildirilmiştir [14,22,23]. Çalışmamızın yapıldığı bölge itibari ile sosyoekonomik olarak yüksek orta seviyede olması, ailelerin yarısından fazlasının eğitim düzeyinin lise ve yüksekokul olması sebebiyle gece altını ıslatmanın tedavi edilmesi gereken bir sağlık sorunu olarak algıladıkları ve bu bilginin büyük kısmının da internet ve TV gibi iletişim araçları üzerinden edinildiği saptanmıştır.…”
Section: Demografikunclassified